2015
DOI: 10.1007/s10047-015-0819-z
|View full text |Cite
|
Sign up to set email alerts
|

Decellularization of porcine carotid by the recipient’s serum and evaluation of its biocompatibility using a rat autograft model

Abstract: Recently, decellularized tissues for organ transplantation and regeneration have been actively studied in the field of tissue engineering. In the decellularization process, surfactants such as sodium dodecyl sulfate (SDS) have been most commonly used to remove cellular components from the tissue. However, the residual surfactant may be cytotoxic in vivo and has been reported to hinder remodeling after implantation. In addition, treatment with surfactants may destroy the important extracellular matrix (ECM) str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…However, it has been shown that even after intense washings of an SDS‐decellularized scaffold, seeded cells do not penetrate and attach (Gratzer et al, ), suggesting that factors other than solely entrapped SDS contribute to the poor engraftment of the cells. SDS has been reported to alter ECM composition, and this modification to the native architecture of the scaffold is likely another cause of reduced recellularization (Gratzer et al, ; Ishino & Fujisato, ; Nichols et al, ; Wong et al, ). Despite the deleterious effects of this detergent, there are reports showing that decellularization with SDS results in a recellularized and functional organ (Song et al, ).…”
Section: Translational Limitations Of Biological Scaffoldsmentioning
confidence: 99%
“…However, it has been shown that even after intense washings of an SDS‐decellularized scaffold, seeded cells do not penetrate and attach (Gratzer et al, ), suggesting that factors other than solely entrapped SDS contribute to the poor engraftment of the cells. SDS has been reported to alter ECM composition, and this modification to the native architecture of the scaffold is likely another cause of reduced recellularization (Gratzer et al, ; Ishino & Fujisato, ; Nichols et al, ; Wong et al, ). Despite the deleterious effects of this detergent, there are reports showing that decellularization with SDS results in a recellularized and functional organ (Song et al, ).…”
Section: Translational Limitations Of Biological Scaffoldsmentioning
confidence: 99%
“…Specifically, we suggest that some of methodologies used to decellularize large-and small-diameter peripheral blood vessels might also be applied for the vascular compartment of whole lungs. In the periphery, these methods yielded excellent preservation of ECM in, e.g., bovine femoral arteries (24), ovine carotid arteries (59), porcine aortic roots (75), and porcine carotid arteries (38). Tissue-engineered vascular grafts made from decellularized peripheral blood vessels have the benefit of containing native vascular ECM proteins but must still overcome problems of mechanical strength and immunogenicity (65).…”
Section: Lessons To Be Learned From Decellularizing Peripheral Blood mentioning
confidence: 99%
“…Tissue-engineered vascular grafts made from decellularized peripheral blood vessels have the benefit of containing native vascular ECM proteins but must still overcome problems of mechanical strength and immunogenicity (65). In some of these studies, decellularization with either 0.1% SDS, autologous/allogeneic serum (i.e., endogenous proteolytic activity from the complement system and endonucleases), or 1% TX resulted in differential preservation of ECM components, higher elastic moduli, and lower compliance of the decellularized vascular grafts compared with native vessels (24,38,59,75). Preservation and/or ease of restoration of the elastance and compliance of the vascular compartment in the lung will have to be integral considerations for future pulmonary decellularization protocols.…”
Section: Lessons To Be Learned From Decellularizing Peripheral Blood mentioning
confidence: 99%
See 2 more Smart Citations